KEPEMIMPINAN PARTISIPATIF KEPALA SEKOLAH DALAM KETERLIBATAN GURU PADA PENGAMBILAN KEPUTUSAN DI SMA NEGERI 13 KOTA JAMBI - Ester Ella Paulina; Mulyadi Mulyadi; Erisa Kurniati (STKIP Pesisir Selatan, 2026)
This study aims to analyze the implementation of participatory leadership by the principal and teacher involvement in decision-making at SMAN 13, Jambi City. The study used a qualitative approach with a case study to gain a deeper understanding of participatory leadership practices in the real school context. Data were collected through open-ended questionnaires, semi-structured interviews, and documentation, then analyzed using the Miles and Huberman model of data reduction, data presentation, and conclusion drawing. The results show that participatory leadership by the principal is implemented through four main aspects: two-way communication, collaboration, teacher involvement, and deliberative decision-making. Teacher involvement has occurred in the planning, implementation, evaluation, academic, and disciplinary development aspects. However, this involvement has not been fully optimal because teachers have not been involved evenly in the initial stages of policy formulation. The novelty of this study shows that teacher involvement is still not comprehensive, resulting in a gap between the practice and concept of participatory leadership. Therefore, it is necessary to strengthen teacher participation to make it more equitable, substantive, and sustainable.